Agent-Based Evolutionary Game Dynamics - Izquierdo, Luis R.; Izquierdo, Segismundo S.; Sandholm, William H.; Open Textbook Library (Open Textbook Library, 2019)
This book is a guide to implement simple agent-based evolutionary models using NetLogo. All the models we implement are agent-based, i.e. individual agents and their interactions are explicitly represented in the models. To formalise agents' interactions we use the basic framework of Evolutionary Game Theory. NetLogo is a multi-agent programmable modeling environment used by hundreds of thousands of students, teachers and researchers all around the globe. No coding experience is necessary to fully understand the contents of this book.
0. Introduction -- 0.1. Introduction to evolutionary game theory -- 0.2. Introduction to agent-based modeling -- 0.3. Introduction to Netlogo -- 0.4. The fundamentals of NetLogo -- 1. Our first agent-based evolutionary model -- 1.0. Our very first model -- 1.1. Extension to any number of strategies -- 1.2. Noise and initial conditions -- 1.3. Interactivity and efficiency -- 1.4. Analysis of these models -- 1.5. Answers to exercises -- 2. Spatial interactions on a grid -- 2.0. Spatial chaos in the Prisoner's Dilemma
In English.
Description based on print resource
Keywords: Computer Science -- Textbooks